2007
DOI: 10.1080/10242420701510460
|View full text |Cite
|
Sign up to set email alerts
|

Chemical thiolation strategy: A determining factor in the properties of thiol-bound biocatalysts

Abstract: Immobilization of enzymes on thiolsulphinate-agarose, a thiol-reactive support, is a unique method which allows reversible covalent immobilization under mild conditions, so excellent immobilization and activity yields are obtained. It allows both the formation of stable bonds as well as enzyme desorption and matrix regeneration. The impact of the source of the enzyme's thiol group involved in the immobilization (native, reduced disulphide or chemically introduced) on the properties of the resulting biocatalyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The other group used to attain an oriented immobilization of enzymes is the thiol group of Cys, immobilizing the enzyme via thiol/disulfide exchange, a very specific reaction that cannot be produced by any other group on the enzyme (Figure ). , Cysteine groups are quite scarce on the protein surface, and when needed, if the native enzyme has some external Cys, it may be transformed into Ser via site-directed mutagenesis, as the physical properties of both lateral chains are somehow similar. To achieve an immobilization fully directed by the Cys location, there are two possibilities: to use thiol reactive disulfide groups on the support , or to generate it on the enzyme (e.g., by modification of the exposed Cys of the enzyme with 2,2-dipyridyl disulfide) (Figure ). , …”
Section: New Tailor-made Heterofunctional Supportsmentioning
confidence: 99%
“…The other group used to attain an oriented immobilization of enzymes is the thiol group of Cys, immobilizing the enzyme via thiol/disulfide exchange, a very specific reaction that cannot be produced by any other group on the enzyme (Figure ). , Cysteine groups are quite scarce on the protein surface, and when needed, if the native enzyme has some external Cys, it may be transformed into Ser via site-directed mutagenesis, as the physical properties of both lateral chains are somehow similar. To achieve an immobilization fully directed by the Cys location, there are two possibilities: to use thiol reactive disulfide groups on the support , or to generate it on the enzyme (e.g., by modification of the exposed Cys of the enzyme with 2,2-dipyridyl disulfide) (Figure ). , …”
Section: New Tailor-made Heterofunctional Supportsmentioning
confidence: 99%
“…Another possible interpretation for this behavior is that the enzyme was attached to the support through a “critical area” for enzyme stability . It has been reported that denaturation of a protein begins in a defined region of the protein called the “critical area”, so when enzymes are immobilized through this area, their stability will be improved …”
Section: Resultsmentioning
confidence: 99%
“…39 It has been reported that denaturation of a protein begins in a defined region of the protein called the "critical area", so when enzymes are immobilized through this area, their stability will be improved. 40 Enzyme Reuses. One of the advantages of enzyme immobilization onto an insoluble support is the possibility of reuse of the enzymatic derivative for consecutive cycles of chitosan hydrolysis.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that denaturation of a protein begins in a defined region of the protein called ‘critical area’. So when enzymes are immobilized through this area, their stability will be improved [44].…”
Section: Discussionmentioning
confidence: 99%